Embracing Protestantism : black identities in the Atlantic world - Catron, John W. (University Press of Florida, 2016)
By examining eighteenth-century black Christianity in multiple locales and tracing the circuits of black evangelicals as they traveled through Africa, the Caribbean, Europe, and North America, Catron examines how many Afro-Protestants maintained cultural and intellectual ties outside the confines of America's plantation complex and suggests they might be better understood as Atlantic Africans.